2007
DOI: 10.1590/s1677-04202007000100006
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the antioxidative enzyme activities and lipid peroxidation in wheat seedlings exposed to cadmium and lead stress

Abstract: Wheat seedlings were grown in presence of CdCl2 (0-200 µM) and Pb(NO3)2 (0-2000 µM) separately. The growth of metal-treated seedlings was significantly depressed. The activities of antioxidative enzymes namely superoxide dismutase (SOD), catalase (CAT) and guaiacol peroxidase (POX) were altered both in root and shoot tissues of 7-d-old seedlings. Under Cd stress, SOD activity in roots was undetectable even at the lowest Cd concentration (50 µM) whereas in shoots it declined sharply with increasing Cd levels. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
50
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(63 citation statements)
references
References 20 publications
10
50
1
2
Order By: Relevance
“…Our results showed that the activity of APX was reduced under Pb and Cd stress, which could be due to its inhibition by these metals, as supported by Das et al (1997), who reported that Cd is a known inhibitor of enzymes. Our results also support the findings of Dey et al (2007), who reported almost complete loss of APX activity in pine roots. Low activity of the APX enzyme showed poor activity of the H 2 O 2 scavenging system, whereas increased activity of antioxidant enzymes is the reflection of metal tolerance.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results showed that the activity of APX was reduced under Pb and Cd stress, which could be due to its inhibition by these metals, as supported by Das et al (1997), who reported that Cd is a known inhibitor of enzymes. Our results also support the findings of Dey et al (2007), who reported almost complete loss of APX activity in pine roots. Low activity of the APX enzyme showed poor activity of the H 2 O 2 scavenging system, whereas increased activity of antioxidant enzymes is the reflection of metal tolerance.…”
Section: Discussionsupporting
confidence: 92%
“…Several researchers found increased protein synthesis under metal stress. Dey et al (2007) observed that under Pb and Cd stress, wheat seedlings had increased protein contents. The increase in protein under Pb stress observed in the present study is in agreement with the findings of Singh et al (2011), who reported an increase in protein in Brassica campestris roots under Pb stress.…”
Section: Discussionmentioning
confidence: 98%
“…The investigations of the heavy metal impact on different plant species showed that various metals, independently of their redox-activity, caused an increase in MDA level [10,18,[36][37][38]. In our study dosedependent increase in MDA content was detected in the leaves of spring barley treated with all investigated metals (Cu, Cd, Cr, Ni, Pb and Zn), however, the level of MDA increase was very different.…”
Section: Oxidative Stress Induced By Different Heavy Metalscontrasting
confidence: 50%
“…This result corroborates with that presented by Mishra and Choudhari (1998) in Pbexposed rice. In fact, Pb toxicity is reported to inhibit growth of several plants (Singh et al, 1997;Mishra et al, 2006;Romeiro et al, 2006;Dey et al, 2007). However, among the different metals tested in cucumber (Cd, Cu, Pb) and in radish (Raphanus sativus) (Cd, Hg, Zn, Pb), Pb was the least toxic to growth of seedlings (Morsch et al, 2002;An et al, 2004).…”
Section: Discussionmentioning
confidence: 99%